Migratory and resident waders differ in risk taking on the wintering grounds - Mikula, Peter; Díaz, Mario; Møller, Anders Pape; Albrecht, Tomáš; Tryjanowski, Piotr; Hromada, Martin (Behavioural processes, 2018)
Animals, including birds, have to optimize their escape strategies under the risk of predation. Level of risk-taking is often estimated as flight initiation distance (FID), which is assumed to reflect the trade-off between costs of escape and benefits of staying put. Despite costs and benefits of escape may change during the season, previous studies have focused mainly on breeding bird populations. Here, we focused on risk taking in migratory and resident populations of waders (Charadriiformes) at the wintering grounds in tropical Africa. Phylogenetically informed comparative analyses revealed significant correlation between starting distance, body mass and, marginally, reproductive effort and FID, but no correlation between flock size and FID in wintering waders. Interestingly, despite no differences in body mass, reproductive effort and flock size, FID significantly differed between migratory and resident wader species after controlling for the potential effect of confounding variables, with FID being shorter in resident species. This suggests that such differences in risk perception are linked to some other factors as, for instance, the level of familiarity of waders with local environments at their wintering grounds and previous experience with humans. Our results may have also implications for avian conservation of migratory species at wintering grounds.
Keywords: migrace zvířat; Flight initiation distance; roční období; Escape strategy; predátorské chování; Predatory Behavior; Charadriiformes; fylogeneze; Seasons; Migration; Animal Migration; riskování; Reproduction; zvířata; Risk-Taking; Animals; rozmnožování; Antipredator behaviour; Phylogeny; Predation risk